Salamanders from the eastern Cordillera de Talamanca, Costa Rica, with descriptions of five new species (Plethodontidae: Bolitoglossa, Nototriton, and Oedipina) and natural history notes from recent expeditions - Boza-Oviedo, Eduardo; Rovito, Sean M.; Chaves, Gerardo; García-Rodríguez, Adrián; Artavia, Luis G.; Bolaños, Federico; Wake, David B. (Zootaxa, 2012)
We describe five new species of lungless salamanders (Plethodontidae) from high mountain habitats along the border betweenCosta Rica and Panama: Bolitoglossa splendida, Bolitoglossa aureogularis, Bolitoglossa kamuk, Nototriton matama, andOedipina nimaso. We also present phylogenetic hypotheses for the new taxa (with the exception of the Oedipina) and their rel-atives based on mitochondrial DNA sequence data. The new species were discovered on a series of expeditions to remote areas (primarily over 1000 m elevation) of the Cordillera de Talamanca, Costa Rica.